Descriptive Analysis of Pediatric Studies Included in the European Union Post-Authorization Study Register from 2010 to 2023 - Annalisa Landi; Giorgio Reggiardo; Antonella Didio; Annunziata D’Ercole; Adriana Ceci; Grace Shalom Govere; Donato Bonifazi; Fedele Bonifazi; Salvatore Crisafulli; Gianluca Trifirò; Florentia Kaguelidou; Katja Marja Hakkarainen; et al. (Pediatric Reports)
Background/Objectives: This work aimed to analyze pediatric Post-Authorization Studies (PASs) registered in the European Union electronic Register of Post-Authorization Studies (EU PAS Register) from September 2010 to April 2023 to identify trends in terms of timing, age groups, and therapeutic areas and to discuss pediatric specificities and sources of funding for the PASs. Methods: A screening process identified PASs conducted exclusively on the pediatric population, and instructions were provided to ensure standardized data collection from the EU PAS Register. A univariate linear regression descriptive analysis was performed to assess trends over time, while a multivariate linear regression analysis helped explore additional characteristics of these studies. Results: Of the 2574 PASs extracted from the EU PAS Registry, 165 were included in this analysis. The majority of pediatric PASs were observational studies (86%), and most of them utilized secondary data (53%). The annual number of PASs increased significantly between 2010 and 2023. As envisaged, the largest part was funded by pharmaceutical companies (62%). Anti-infectives for systemic uses (25%), medicines for the nervous system (18%), and antineoplastic and immunomodulating agents (15%) resulted in the most studied drugs. Conclusions: Our findings show that post-marketing observational research in pediatric populations has increased over time. Nevertheless, industry–academia collaboration should be encouraged, and regulatory guidance is needed to prioritize research in areas of unmet therapeutic need.